PERGESERAN PENERJEMAHAN IDIOM PADA NOVEL ODA NOBUNAGA KARYA SOHACHI YAMAOKA - Ayu Muliani, Putu (Humanis, 2016)
This research describes transposition and modulation of idiom translation from idiom using part of body and feelings (ki)found inSohachi Yamaoka’s novel Oda Nobunaga. This research used the equivalence intralingual method. The analysis of data based on the theory of transposition by Catford (1965), and modulation by Newmark (1988). 31 idioms have been found as the result of the analysis. The type of transposition from 26 data are 7data of level shift, 5 data of structure shift, 1 data of class shift and 12 data of unit shift. The type of modulation from 12 data are 2 data of cause effect, 1 data of one part of another, 6 data of active for passive, and 3 data of positive for double negative.From all of the idiom data’s, unit shift is the most used in the idiom translation and there are 7 idioms used transposition and modulation.
Keywords: idiom translation, transposition, modulation